ROS regulates circadian rhythms by modulating Ezh2 interactions with clock proteins - Hao-yi Zhang; Ke-yun Li; Yi-li Wang; Chun-Jiao Wei; Yu-Xuan Gao; Ren-Zhou; Ying-bin Zhong; Zong-jun Yin; Da-long Ren (Redox Biology)
Redox imbalance induced by the accumulation of reactive oxygen species (ROS) accelerates age-related processes, often accompanied by a decrease in circadian rhythm amplitude. However, the underlying mechanisms by which ROS modulate circadian rhythms remain poorly understood. In this study, we found that ROS disrupt circadian rhythms in both zebrafish, as indicated by changes in diurnal behavior and clock gene expression, and in a human cell model. Using weighted gene co-expression network analysis (WGCNA) and machine learning approaches (RF, LASSO, SVM), EZH2 was identified as a key gene involved in regulating circadian rhythms under oxidative stress conditions. To further investigate the role of EZH2, we employed ezh2−/− mutants, Morpholino injection, and overexpression treatment and discovered that EZH2 is crucial in mediating the effect of ROS on circadian rhythms. Furthermore, EZH2 interacts with the CLOCK-BMAL1 complex to regulate the transcription of clock genes, as demonstrated through co-immunoprecipitation (co-IP), chromatin immunoprecipitation (ChIP), and dual-luciferase reporter assays. Our study revealed that ROS disrupt circadian rhythms by regulating the interaction between EZH2 and the CLOCK-BMAL1 complex, shedding light on the molecular mechanisms of circadian rhythm disruption under oxidative stress and suggesting potential targets for age-related and circadian disorders.